C-X-C RECEPTOR 4 CXCR4 METASTASIS KANKER PAYUDARA - I Wayan Sudarsa; I Wayan Putu Sutirta Yasa (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
The chemokine receptors CXCR4 (chemokine C-X-C motif receptor 4) and its ligand (stromal derived factor-1/SDF-1 or chemokinemotif ligand 12/CXCL12) play an important role in cancer invasion and metastasis. The spread of breast cancer follows a nonrandommetastatic pattern typically involving spread of tumor to regional lymph nodes, lung, liver, and/or bone marrow. The ligand for CXCR4,SDF-1/CXCL12, is highly expressed by stromal fibroblasts within these tissues. The chemokine receptors CXCR4 is structurally related tochemokine receptor belonging to the superfamily of the seven transmembrane G-protein coupled receptors. In contrast to normal breasttissue, breast cancer cells typically express high levels of functional CXCR4 receptors that can direct chemotaxis and invasive responses.Expression of SDF-1/CXCL-12 in turn, promotes the progression of breast cancer by directly enhancing tumor-cell growth and by recruitingendothelial progenitor cells that are required for tumor angiogenesis. High-level expression of CXCR4 on neoplastic cells is associated withrelatively poor overall survival and bad prognosis in patients with breast cancer. The promising results in the preclinical tumor modelsindicate that CXCR4 antagonists may have to reduce the spread of cancer that is called anti tumor activity in patients with breast cancer.The chemokine receptors CXCR4 antagonists, although initially developed for treatment of acquired immunodeficiency diseases syndrome(AIDS), actually may become effective agents as a molecular targeted therapy for breast cancer.